Advances in Endoscopic Visualization of Barrett’s Esophagus: The Role of Confocal Laser Endomicroscopy - Helga Bertani; Flavia Pigò; Emanuele Dabizzi; Marzio Frazzoni; Vincenzo Giorgio Mirante; Mauro Manno; Raffaele Manta; Rita Conigliaro (Gastroenterology Research and Practice)
Many endoscopic imaging modalities have been developed and introduced into clinical practice to enhance the diagnostic capabilities of upper endoscopy. In the past, detection of dysplasia and carcinoma of esophagus had been dependent on biopsies taken during standard white-light endoscopy (WLE). Recently high-resolution (HR) endoscopy enables us to visualize esophageal mucosa but resolution for glandular structures and cells is still low. Probe-based confocal laser endomicroscopy (pCLE) is a new promising diagnostic technique by which details of glandular and vascular structures of mucosal layer can be observed. However, the clinical utility of this new diagnostic tool has not yet been fully explored in a clinical setting. In this paper we will highlight this new technique for detection of esophageal dysplasia and carcinoma from a clinical practice perspective.